Comparative Efficacy of Pharmacological Treatment of Absence Epilepsy with Typical and Deviating (Complex) EEG Patterns - Maloletnev, V.I.; Gugushvili, M.L.; Khachidze, I.O. (Нейрофизиология, 2016)
In a group of 96 children and teenagers suffering from absence epilepsy, we compared the
efficacy of treatment with a valproic acid derivative, Depakin (D). In 72 patients of group 1,
EEGs contained bursts of typical absence seizure phenomena, generalized 3–4 Hz spike/wave
complexes, SWCs. In 24 patients of group 2, these EEG phenomena were combined with
other types of epileptiform elements (generalized and focal irregular peak/wave complexes,
single and grouped sharp waves, spikes, polyspikes, etc.). It was found that pharmacotherapy
with D effectively eliminated SWCs generated in the resting state of the patients; epileptiform
phenomena provoked by hyperventilation and rhythmic photostimulation were noticeably
more resistant from this aspect. The efficacy of treatment with D was considerably higher
in group 1 (patients with the EEG patterns including only SWCs) than in group 2 (patients
with deviating EEG patterns containing, together with SWCs, epileptiform elements of other
types). Six months after the D therapy initiation, complete elimination of typical 3-4 Hz
SWCs was observed in 63.9% of group-1 patients and in 41.7% of group-2 patients. У групі з 96 дітей та підлітків, що страждали на абсансну
епілепсію, ми порівнювали ефективність лікування з використанням похідного вальпроєвої кислоти депакіну (Д). У
72 пацієнтів групи 1 в ЕЕГ були присутні типові феномени
абсансної судомної активності – генералізовані комплекси
пік/хвиля (SWC, 3–4 Гц). У 24 пацієнтів такі ЕЕГ-феномени
комбінувалися з епілептиформними елементами інших типів (генералізованими та фокальними нерегулярними комплексами пік/хвиля, поодинокими та груповими гострими
хвилями, ЕЕГ-піками, множинними піками і т. д.). Як виявилося, фармакотерапія з використанням Д ефективно усувала SWC, генеровані в спокійному стані пацієнтів; епілептиформні ЕЕГ-феномени, провоковані гіпервентиляцією та
ритмічною фотостимуляцією, були помітно більш опірними
в цьому аспекті. Ефективність лікування за допомогою Д в
групі 1 (пацієнти з наявністю виключно SWC у складі ЕЕГ)
була істотно вищою, ніж у групі 2 (пацієнти з девіантними
ЕЕГ-патернами, котрі містили в собі комбінації епілептиформних елементів інших типів із SWC). Через шість місяців після початку прийому Д типові SWC (3–4 Гц) повністю
зникали з ЕЕГ 63.9 % пацієнтів групи 1 та 41.7 % пацієнтів групи 2.